Frequency, severity, and distress of dialysis-related symptoms reported by patients on hemodialysis - Danquah, Francess Victoria Nelson; Zimmerman, Lani; Diamond, Pamela M; Meininger, Janet; Bergstrom, Nancy (Nephrology nursing journal : journal of the American Nephrology Nurses' Association, 2010)
The purpose of this study was to determine which symptoms are the most reported occur most frequently, have the greatest severity, and cause the most bother for patients on hemodialysis (HD), and to determine if the symptoms experienced differ between the first (HD1) and second (HD2) treatments of the week. An observational, comparative design was used to determine participants' HD symptoms experienced on HD1 and HD2, and the effect of the symptom experience on quality of life (QOL). One hundred subjects were recruited from five dialysis centers. The adapted Dialysis Frequency, Severity, and Symptom Burden Index (DFSSBI) and the Medical Outcomes Study Short Form 36 (MOS SF 36) were administered (N = 99) on HD1 and the DFSSBI again on HD2. Data were analyzed for significance among symptom experience test scores in relation to HD1 and HD2, QOL, and gender and age. Of 31 symptoms assessed respondents reported an average of 9.77 symptoms on HD1 and 7.51 symptoms on HD2. Overall, more symptoms were reported and were more frequent, severe, and bothersome on HD1 when the level of metabolic waste is highest. The most reported symptoms included tiredness, dry skin, difficulty falling asleep, itching, numbness/tingling, difficulty staying asleep, decreased interest in sex, and bone/joint pain. Females scored consistently higher than males in the four symptom dimensions. Respondents reported about the same as the population norm (50) on the physical component summary score of the MOS SF 36 and higher than the norm (65.23) on the mental component summary score. The study found patients on HD experience multiple symptoms that can be frequent, severe, and bothersome. Interventions should be developed and tested to reduce symptom bother and improve QOL.